Fluorescence lifetime imaging for studying DNA compaction and gene activities - Svitlana M. Levchenko (Nature Publishing Group, 2021)
Abstract Optical imaging is a most useful and widespread technique for the investigation of the structure and function of the cellular genomes. However, an analysis of immensely convoluted and irregularly compacted DNA polymer is highly challenging even by modern super-resolution microscopy approaches. Here we propose fluorescence lifetime imaging (FLIM) for the advancement of studies of genomic structure including DNA compaction, replication as well as monitoring of gene expression. The proposed FLIM assay employs two independent mechanisms for DNA compaction sensing. One mechanism relies on the inverse quadratic relation between the fluorescence lifetimes of fluorescence probes incorporated into DNA and their local refractive index, variable due to DNA compaction density. Another mechanism is based on the Förster resonance energy transfer (FRET) process between the donor and the acceptor fluorophores, both incorporated into DNA. Both these proposed mechanisms were validated in cultured cells. The obtained data unravel a significant difference in compaction of the gene-rich and gene-poor pools of genomic DNA. We show that the gene-rich DNA is loosely compacted compared to the dense DNA domains devoid of active genes.